1996
DOI: 10.1074/jbc.271.41.25575
|View full text |Cite
|
Sign up to set email alerts
|

Stonustoxin Is a Novel Lethal Factor from Stonefish (Synanceja horrida) Venom

Abstract: Stonustoxin (SNTX) is a multifunctional lethal protein isolated from venom elaborated by the stonefish, Synanceja horrida. It comprises two subunits, termed ␣ and ␤, which have respective molecular masses of 71 and 79 kDa. SNTX elicits an array of biological responses both in vitro and in vivo, particularly a potent hypotension that appears to be mediated by the nitric oxide pathway. As a prelude to structure-function studies, we have isolated and sequenced cDNA clones encoding the ␣-and ␤-subunits of SNTX fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
63
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 43 publications
3
63
1
Order By: Relevance
“…These symptoms include endothelium-dependent vasorelaxation, hemolytic activity, edema, increases in vascular permeability, myotoxic effects on the neuromuscular junction, and severe pain (1,3). By revealing that SNTX and related proteins are poreforming proteins of the MACPF/CDC superfamily, our data provide the structural and molecular context for the unique physiological effects of stonefish envenomation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These symptoms include endothelium-dependent vasorelaxation, hemolytic activity, edema, increases in vascular permeability, myotoxic effects on the neuromuscular junction, and severe pain (1,3). By revealing that SNTX and related proteins are poreforming proteins of the MACPF/CDC superfamily, our data provide the structural and molecular context for the unique physiological effects of stonefish envenomation.…”
Section: Discussionmentioning
confidence: 99%
“…The lethal factor in stonefish venom is an ∼150-kDa protein termed stonustoxin (SNTX), an unusual example of a vertebrate cytolytic protein complex (2). SNTX is a soluble heterodimeric assembly of two closely related proteins termed SNTX-α and -β that share sequence identity of ∼50% (3). With the exception of a C-terminal PRY SPla and the RYanodine Receptor (PRYSPRY) domain in each protein (4), SNTX shares no obvious sequence similarity to any structurally or functionally characterized molecule.…”
mentioning
confidence: 99%
“…2). Previous studies suggested that the amphiphilic structures of some cytolytic protein toxins allow the formation of pores in cell membranes, [11][12][13] and thus the amphiphilic structures of the box jellyfish toxins may explain their potent hemolytic activity (Table 1).…”
Section: Comparison Of Proteinaceous Toxins Obtained From Box Jellyfishmentioning
confidence: 99%
“…1). The SPRY domain is present for example in butyrophilin-related transmembrane glycoproteins (BTN) [3] and in stonustoxin SNTX, a cytolytic secreted protein [4]. Another set of proteins containing a SPRY domain are SSB proteins (SPRY domain associated with a SOCS box) belonging to the family of suppressors of cytokine signaling (SOCS) [5].…”
Section: Introductionmentioning
confidence: 99%